2016
DOI: 10.1093/tropej/fmw071
|View full text |Cite
|
Sign up to set email alerts
|

Improved Neonatal Mortality at a District Hospital in Aweil, South Sudan

Abstract: Neonatal deaths comprise a growing proportion of global under-five mortality. However, data from the highest-burden areas is sparse. This descriptive retrospective study analyses the outcomes of all infants exiting the Médecins sans Frontières-managed neonatal unit in Aweil Hospital, rural South Sudan from 2011 to 2014. A total of 4268 patients were treated over 4 years, with annual admissions increasing from 687 to 1494. Overall mortality was 13.5% (n = 576), declining from 18.7% to 11.1% (p for trend <0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 18 publications
11
20
0
Order By: Relevance
“…Birth asphyxia, preterm, low birth weight, and failure to initiate early feeding were significant factors that increased the likelihood of neonatal deaths. These findings are consistent with previous studies in Ethiopia and other countries, in which intrapartum and neonatal conditions were found to be important predictors of neonatal mortality [21,25,28,[30][31][32][33]. Preterm and low birth weight babies were more likely to be prone to complications such as hypothermia, infections, and birth asphyxia (resulting in tissue hypoxia and multi-organ failure).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Birth asphyxia, preterm, low birth weight, and failure to initiate early feeding were significant factors that increased the likelihood of neonatal deaths. These findings are consistent with previous studies in Ethiopia and other countries, in which intrapartum and neonatal conditions were found to be important predictors of neonatal mortality [21,25,28,[30][31][32][33]. Preterm and low birth weight babies were more likely to be prone to complications such as hypothermia, infections, and birth asphyxia (resulting in tissue hypoxia and multi-organ failure).…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, the main causes of death were complications of preterm birth (28.58%), birth asphyxia (22.45%), and neonatal infection (18.36%). This was supported by reports and findings from the WHO, Northern Vietnam, India, Ghana, Nigeria, Cameroon, South Sudan, and Southern and Northern Ethiopia [5,11,19,20,[22][23][24][26][27][28][29][30]. The findings of our study showed that more than 70% of neonatal deaths were attributed to prematurity, neonatal sepsis, and birth asphyxia.…”
Section: Discussionsupporting
confidence: 90%
“…Women from remote health clinics with obstetric emergencies and sick newborns may have experienced delays in reaching a provincial hospital, so are in poorer condition on arrival. The delays in problem recognition, seeking care, transport delays and facility delays have been well described as well as poorer outcomes in ‘out‐born’ neonates into referral centres . This local referral bias, and onward referral obstacles, are likely to partly account for the higher mortality rates in provincial hospitals compared to the tertiary centre.…”
Section: Discussionmentioning
confidence: 99%
“…19 SCNUs that are supported by other actors showed a reduction in intra-ward mortality: a Mozambican SNCU supported by Collegio Universitario Aspiranti Medici Missionari-Doctors for Africa brought mortality down from 26% to 13%, 8 and an MSF-managed SNCU in South Sudan (not included in this study), which excluded babies weighing 1250 g from admission, reported a reduction of mortality from 19% to 11% within 3 years. 10 Facility exit outcomes of neonatal units not only reflect the quality of nursing and medical care at the unit, they are also highly dependent on the patient population and on the quality of intrapartum and immediate post-partum interventions. A neonatal unit adjacent to a maternity unit offering comprehensive emergency obstetric care and acting as a referral centre for complicated deliveries will receive a high number of severely sick neonates.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…The set-up of these units has been described in detail elsewhere. 9,10 Despite the differences in contexts, the care package offered is similar across all SNCUs. Patient management is carried out in accordance to standardised MSF-OCB neonatal guidelines, and paediatric guidance is provided by the MSF Headquarters.…”
mentioning
confidence: 99%